2007
DOI: 10.1029/2006jc003505
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of submarine groundwater discharge along the continental shelf of Louisiana using a multiple tracer approach

Abstract: [1] Natural geochemical tracers ( 222 Rn, 3 H, 3 He, and 4 He) were used to assess submarine groundwater discharge (SGD) along the continental shelf west of the Mississippi River. In order to assess SGD, groundwater, surface water, and sediment samples were collected on land and during six 4-day cruises aboard the R/V Pelican between March 2003 and May 2004. A box model approach was used to quantify sources and sinks of 222 Rn in the study area and to calculate SGD rates. SGD estimates were we based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
4
19
0
Order By: Relevance
“…Rather the near-shore coastal zone serves as a groundwater recharge area of saline water that then forms the seawater recirculation system beneath the coastal plain. The modeling results are consistent with interpretations of the rates of submarine groundwater discharge derived from geochemical tracers, presented in a companion paper by McCoy et al (2007). …”
supporting
confidence: 88%
See 4 more Smart Citations
“…Rather the near-shore coastal zone serves as a groundwater recharge area of saline water that then forms the seawater recirculation system beneath the coastal plain. The modeling results are consistent with interpretations of the rates of submarine groundwater discharge derived from geochemical tracers, presented in a companion paper by McCoy et al (2007). …”
supporting
confidence: 88%
“…[41] Results of the geochemical tracer study reported by McCoy et al [2007] yield interpretations consistent with the estimates derived from hydrogeological modeling. Both approaches indicate no SGD immediately offshore of coastal Louisiana.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations